2002
DOI: 10.1095/biolreprod66.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids Affect the Testicular Androgen Production in Male Common Carp (Cyprinus carpio L.)1

Abstract: Our previous experiments to study the effect of stress adaptation on pubertal development in carp showed that repeated temperature stress and prolonged feeding with cortisol-containing food pellets, which mimics the endocrine stress effects, retarded the first waves of spermatogenesis and decreased 11-ketotestosterone (11KT) plasma levels. The objective of the present study was to investigate whether the decrease in plasma 11KT is caused by a direct effect of cortisol on the steroid-producing capacity of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 31 publications
0
21
0
2
Order By: Relevance
“…Stress can act at multiple levels to disrupt breeding, including at the brain, the pituitary, and directly at the level of the gonads (Consten et al 2002, Michael et al 2003, Breen and Karsch 2006, Oakley et al 2009, Schoech et al 2009). In House Sparrows, we found evidence of seasonal regulation of CORT receptors in whole brain, but not in hippocampus or gonads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress can act at multiple levels to disrupt breeding, including at the brain, the pituitary, and directly at the level of the gonads (Consten et al 2002, Michael et al 2003, Breen and Karsch 2006, Oakley et al 2009, Schoech et al 2009). In House Sparrows, we found evidence of seasonal regulation of CORT receptors in whole brain, but not in hippocampus or gonads.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is significant GR and MR binding in House Sparrow testes and ovary (Lattin et al 2012b), and CORT can suppress steroidogenesis and other reproductive processes by acting directly on the gonads (Hsueh and Erickson 1978, Sapolsky 1985, Consten et al 2002, 11β hydroxysteroid dehydrogenase type 2, which converts CORT into an inactive metabolite, may also be present in these tissues, as it is in the gonads of other animals (Michael et al 1993, Monder et al 1994, Denari and Ceballos 2005. This may prevent CORT from binding to gonadal GR and MR in situations of short-term stress and could be the reason that the short-term down-regulation of reproduction by stress seems to happen primarily via regulation at the brain and pituitary (Rivier andRivest 1991, Breen andKarsch 2006).…”
mentioning
confidence: 99%
“…Moreover, a negative correlation was found between the nuclear area of steroidogenic cells and 11-KT plasma levels exclusively in NT males. Consten et al (2002) have proposed that, in the teleost fish Cyprinus carpio, cortisol sensitivity depends on the reproductive maturational status of the animal. It is probable, however, that in the C. dimerus' NT males, but not in T males, cortisol levels reached the threshold to produce a concentration-dependent decrease in plasma 11-KT levels.…”
Section: Interrenal Gland and The Establishment Of Social Hierarchiesmentioning
confidence: 99%
“…We propose to consider 11-KT as the physiologically most important androgen of the group of 11-oxygenated steroids produced by zebrafish testis, in particular because 11-KT holds the most downstream position in the steroidogenic pathway. In closely related species, such as goldfish (Carassius auratus; Abdullah & Kime 1994) or common carp (Barry et al 1990), 11-oxygenated teleost androgens have been identified as main products of testicular steroidogenesis, such as 11-KT in goldfish, or OA in common carp, which can either be converted to 11-KT by Hsd17b activity residing in erythrocytes of many fish species (Mayer et al 1990), or is directly produced by carp testis tissue with an efficiency increasing during pubertal maturation (Consten et al 2002), suggesting that an increasing Hsd17b activity (i.e., conversion of OA to 11-KT) is one of the factors associated with puberty. A testicular hsd17b type 3 cDNA has been identified recently in zebrafish (Mindnich et al 2005), which converted OA to 11-KT.…”
Section: Zebrafish Androgen Receptormentioning
confidence: 99%